Do we react differently toward bionic devices vs. cochlear implants and wheelchairs? Possible links with personality traits - Oancea-Matei, Diana-Alina; Gherguț, Alois; Maftei, Alexandra (Frontiers in Rehabilitation Sciences, 2023)
The present study explored the attitudes toward individuals with bionic eyes and limbs, cochlear implants, and people with disabilities that imply using a wheelchair. Our sample consisted of 474 Romanian adults aged 18 to 61 (M = 27.56, SD = 11.80). Participants were randomly divided into five groups. They all filled scales related to personality characteristics, i.e., agreeableness, neuroticism, openness to experience, comprehension/ intellectual efficiency, and previous contact with disability. Then, each group was presented with a vignette describing a character (wheelchair / bionic eye / bionic leg / cochlear implant/control group). Finally, they answered questions about their emotions, cognitions, and behaviors related to that context. Overall, our results suggested that higher agreeability, extraversion, openness to experience, intellectual complexity, and lower neuroticism were generally associated with more positive attitudes toward disability. When examining the differences in participants' emotions, cognitions, and behaviors depending on the target's characteristics, our results generally suggested that the most negative reactions were toward the character with a bionic eye. We discuss these findings considering their importance for shaping positive attitudes related to disability, especially related to the future technological advances in bionic devices.